PERJANJIAN ANTARA CALON JAMAAH HAJI DAN KBIH HIJR ISMAIL TERKAIT BIMBINGAN HAJI MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2008 TENTANG PENYELENGARAAN IBADAH HAJI - JERRY ASTIA SIAHAAN (PREMISE LAW JURNAL, 2017)
Pilgrimage is one of the compulsory rituals in the Islamic doctrine. The place is in the Arabic land which has already been determined by Allah SWT. To support the good and correct pilgrimage performance, some institutions provide some pilgrimage counseling services through Groups of Pilgrimage Counseling Services known as KBIH; the private organizers as the extended hands of the Ministry of Religion; the executor of the laws in providing pilgrimage counseling services. The research problems are why the agreement between KBIH Hijr Ismail and their customers is not written, what problems occur in carrying out the pilgrimage counseling services, and how the responsibilities of the Ministry of Religion related to the controls on the pilgrimage counseling services provided by KBIH Hijr Ismail are. The research method is descriptive qualitative using primary and secondary data and juridical normative and empirical methods.The results show that KBIH Hijr Ismail does not make a written agreement because it is more practical and does not need a high cost. The late pilgrimage practice and small amount of fund in one pilgrimage practice are the problems that occur between KBHI Hijr Ismail and their customers. The responsibilities of the Ministry of Religion related to the controls on the pilgrimage counseling service provided by KBIH Hijr Ismail is by controlling the KBIH. Because there are so many KBIH in every region of the Ministry of Religion, it is very possible that they may perform the counseling out of their duties and functions as the organizers of the pilgrimage counseling services. In other words, they also perform the duties of the executors of pilgrimage rituals.